2019
DOI: 10.3390/ma12213477
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-PEDOT: PSS Humidity Sensors for High Sensitive, Low-Cost, Highly-Reliable, Flexible, and Printed Electronics

Abstract: A comparison of the structure and sensitivity of humidity sensors prepared from graphene (G)-PEDOT: PSS (poly (3,4-ethylenedioxythiophene)) composite material on flexible and solid substrates is performed. Upon an increase in humidity, the G: PEDOT: PSS composite films ensure a response (a linear increase in resistance versus humidity) up to 220% without restrictions typical of sensors fabricated from PEDOT: PSS. It was found that the response of the examined sensors depends not only on the composition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Various printed sensors are reported in the literature, e.g., carbon nanotube (CNT) based gas sensors [13], graphene-poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) humidity sensors [48], PEDOT:PSS based temperature sensors [49,50] and active matrix sensor arrays printed on flexible substrate comprising organic TFTs, organic photodiodes [13]. Recent developments on organic inks and lignocellulosic substrates have demonstrated the printability of biocompatible and/or recyclable sensing devices.…”
Section: Sensorsmentioning
confidence: 99%
“…Various printed sensors are reported in the literature, e.g., carbon nanotube (CNT) based gas sensors [13], graphene-poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) humidity sensors [48], PEDOT:PSS based temperature sensors [49,50] and active matrix sensor arrays printed on flexible substrate comprising organic TFTs, organic photodiodes [13]. Recent developments on organic inks and lignocellulosic substrates have demonstrated the printability of biocompatible and/or recyclable sensing devices.…”
Section: Sensorsmentioning
confidence: 99%
“…The response time can be defined as the time required for a sensor output to adjust to 90% of its final settled value from its previous state. The sensor's recovery time is defined as the time required for the sensor output to decrease to 10% of the final settled value [18]. The values of response and recovery time for each sensor are illustrated in Table-1.…”
Section: Resultsmentioning
confidence: 99%
“…To address the power consumption and system integration issues in the chemical/gas sensors, the combination of self‐powered ability and flexibility in the sensor has attracted increasing research interests recently. For example, to accurately evaluate the wellbeing conditions of a person, a smart and multifunctional textile based on a simple dip‐coating method is illustrated in Figure 2D 104,105 . It is shown that a maximum output power density of 2 Wm −2 can be realized with a polymer‐coated textile, which also possesses good CO 2 sensing response.…”
Section: General Wearable Electronics and Wearable Photonicsmentioning
confidence: 99%